Methylglyoxal Impairs the Pro-Angiogenic Ability of Mouse Adipose-Derived Stem Cells (mADSCs) via a Senescence-Associated Mechanism - Alessia Leone; Antonella Nicolò; Immacolata Prevenzano; Federica Zatterale; Michele Longo; Antonella Desiderio; Rosa Spinelli; Michele Campitelli; Domenico Conza; Gregory Alexander Raciti; Francesco Beguinot; Cecilia Nigro; et al. (Cells, 2023)
Adipose-derived stem cells (ADSCs) play a crucial role in angiogenesis and repair of damaged tissues. However, in pathological conditions including diabetes, ADSC function is compromised. This work aims at evaluating the effect of Methylglyoxal (MGO), a product of chronic hyperglycemia, on mouse ADSCs’ (mADSCs) pro-angiogenic function and the molecular mediators involved. The mADSCs were isolated from C57bl6 mice. MGO-adducts and p-p38 MAPK protein levels were evaluated by Western Blot. Human retinal endothelial cell (hREC) migration was analyzed by transwell assays. Gene expression was measured by qRT-PCR, and SA-βGal activity by cytofluorimetry. Soluble factor release was evaluated by multiplex assay. MGO treatment does not impair mADSC viability and induces MGO-adduct accumulation. hREC migration is reduced in response to both MGO-treated mADSCs and conditioned media from MGO-treated mADSCs, compared to untreated cells. This is associated with an increase of SA-βGal activity, SASP factor release and p53 and p21 expression, together with a VEGF- and PDGF-reduced release from MGO-treated mADSCs and a reduced p38-MAPK activation in hRECs. The MGO-induced impairment of mADSC function is reverted by senolytics. In conclusion, MGO impairs mADSCs’ pro-angiogenic function through the induction of a senescent phenotype, associated with the reduced secretion of growth factors crucial for hREC migration.